Economic violence against women in Croatia : a comparative study between continental and maritime county - Miškulin, Ivan (Array, 2020)
Economic violence (EV) refers to acts of control and monitoring of the behavior of an individual in terms of the use and distribution of money, and the constant threat of denying economic resources. EV has hindered a great proportion of women from achieving economic autonomy and sustainable livelihood for themselves and their dependents. The aim of this study was to examine the prevalence of EV among Croatian women, to identify the main forms of EV and to evaluate interconnection between EV and selected sociodemographic indicators. As part of this cross-sectional study a validated, anonymous questionnaire that contained questions regarding sociodemographic data as well as questions regarding EV was self-administered to a sample of women from two Croatian counties, one continental (Osijek-Baranja) and one maritime (Istria), during April and May 2017. The study sample included 1314 women, the median age being 41 (interquartile range 32–55) years. The overall prevalence of EV was 18.9%; 77.5% being qualified as less and 22.5% as more severe. Among the women who experienced EV 96.0%, 59.8% and 36.1% of them were exposed to economic control, economic exploitation and employment sabotage, respectively. The EV was more prevalent among women from maritime (Istria) county (P<0.001); women aged between 44 and 56 years and women aged between 31 and 43 years (P<0.001); women who were single (P<0.001); women with lower educational level (P=0.006) and women with under average self perceived socioeconomic status (P<0.001). It can be concluded that EV is highly prevalent among Croatian women and as such represents an important public health challenge within this population. Selected sociodemographic indicators represent significant risk factors for the development of EV in the studied population.